Tracing early life on Mars: lessons from organics produced in high-altitude hotsprings of Ladakh - Arif Husain Ansari; Arunaditya Das; Nasreen Ghazi Ansari; Archana Sonker (Progress in Earth and Planetary Science)
Abstract Hotspring waters have traditionally been recognized for their therapeutic benefits. More recently, high-altitude hotsprings have received attention for astrobiological studies because they replicate several parameters of extreme conditions that once occurred on early Mars. Investigation of such hotspring environments can provide us with more relevant biomarker tools to study the search for possible extinct life on Mars that existed in similar environments. This study presents the first qualitative data (semiquantitative) on organic compounds’ origin and distribution in Ladakh’s high-altitude hotspring waters. The study was conducted on the Chumathang, Panamik, Changlung, and Puga hotspring sites with thermal water temperatures and pH ranging from 50.4° to 84.9 °C and 7.01 to 8.08, respectively. These sites were dominated by bacterially produced organic compounds, mainly n-alkanes, esters, alcohols, carboxylic acids, and alkenes. Non-distinguishable thermogenic abiotic organic compounds may represent a minor fraction of low molecular weight n-alkanes (C12 and C14). A semiquantitative understanding of organic compounds based on peak area percentage exhibits that larger proportions of organic compounds in the thermal waters of these sites were dominated by a diverse range of bioactive compounds in response to various extreme environmental factors. Compared to the low-altitude hotspring waters, the high-altitude hotspring waters contain a significantly higher number of bioactive compounds. These compounds are stable both chemically and physically in the extreme environments commonly found in high-altitude hydrothermal environments, which makes them promising candidates as biomarkers for the search for early life in Mars’ hydrothermal deposits.